PENGARUH CERITA BUDAYA BIMA UNTUK MENINGKATKAN KETERAMPILAN STORYTELLING PADA PELAJARAN BAHASA INDONESIA KELAS IV DI SDN INPRES KAMBILO - Putri Irma Suryani; Nunung Fatimah; Ayub Qadhafi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This ponder points to examine the impact of using Bima cultural folktales on improving storytelling skills among fourth-grade students at SDN Inpres Kambilo. The research was motivated by the students' low speaking ability in delivering stories coherently and expressively. The study applied a quantitative approach with a one-group pretest-posttest design involving 12 students as participants. Instruments included expert material validation questionnaires, teacher and student observations, and storytelling performance tests. The material validity reached a "very valid" level with a total score of 94%. The average student score increased from 35.42 (pretest) to 85.42 (posttest). A paired sample t-test revealed a significance value of 0.000 (p < 0.05), indicating a significant difference after the intervention. These results suggest that integrating local culture-based stories such as Mpa’a Ntumbu Tuta and Wura Bongi Monca can serve as an effective teaching strategy to enhance storytelling skills and foster students’ appreciation of regional heritage.